STUDENTS MOTIVATION FOR SPORTS AND THEIR EVALUATION OF SCHOOL - Nenad Suzić (University of Banja Luka, Faculty of physical education and sport, 2011)
In this survey a sample of 312 students of primary school aged 8 - 14 years was used to test the hypothesis if the motivational profile predetermines sport activities and a success in Physical Educa-tion (PE) classes. After a factorisation and crossing of the components of external and internal motivation, the author extracted three motivational profiles of actors in sports activities: internal motivated, joint motivated and external motivated. It turned out that these profiles significantly de-termine if the kids will play sports, but yet not significantly on their success in PE. These findings are not in favour of PE and they show the need for teachers to try to reduce external, and support the internal student's motivation. Significant finding of this survey is also the fact that as older they get the positive evaluation and experience of school is dropping down. This is especially important if we have in mind that by factorization is determined that for the students the first by its importance in PE is the enjoyment and self-improvement, and that two negative motivational factors are right after them. Besides significant findings, this survey offers some new dilemmas for further research and study.